2020
DOI: 10.17161/kjm.v13i.14565
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Self-Efficacy and Dietary Patterns among Older African American Women in Kansas

Abstract: Introduction. Nutrition is the key contributor to disparities in many chronic diseases. However, little is known about the dietary habits and nutrition self-efficacy beliefs of older African American women with chronic diseases. This study looked at the relationship between nutrition self-efficacy and dietary patterns among older African American women. Methods. A total of 115 African American women 55 years and older, with one or more chronic diseases such as hypertension, diabetes, and hyperlipidemia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Patients with gastric cancer who showed a higher self-efficacy in F&V intake and diet planning showed higher readiness for changes in F&V intake and adhering to a food plan. Although few studies till date have evaluated the relationship between self-efficacy and dietary behaviors in gastric cancer survivors, our findings were consistent with those of studies on African American breast cancer survivors, 41 African American women, 42 adolescents, 43 and a low-income population, 44 which showed that self-efficacy for healthy eating behaviors showed a positive association with diet quality or pattern. Similarly, self-efficacy showed a positive association with healthy eating behaviors, including the selection of healthier foods.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with gastric cancer who showed a higher self-efficacy in F&V intake and diet planning showed higher readiness for changes in F&V intake and adhering to a food plan. Although few studies till date have evaluated the relationship between self-efficacy and dietary behaviors in gastric cancer survivors, our findings were consistent with those of studies on African American breast cancer survivors, 41 African American women, 42 adolescents, 43 and a low-income population, 44 which showed that self-efficacy for healthy eating behaviors showed a positive association with diet quality or pattern. Similarly, self-efficacy showed a positive association with healthy eating behaviors, including the selection of healthier foods.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, changes in self-efficacy level associated with decreases in dietary fat intake in low-income subjects with excess weight have been reported [ 48 ]. Furthermore, a positive correlation between fruit and vegetable intake and high self-efficacy among African American women was reported [ 49 ]. A meta-analysis that assessed behavior techniques to promote self-efficacy found that dietary interventions focusing on self-monitoring, feedback on performance, revision of behavioral goals, provided rewards, or planned social support increased dietary self-efficacy significantly more than interventions that did not [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that some participants reported success in replacing potatoes in a potato salad with cauliflower suggests the importance of culture in food choices. Endorsing success stories can promote confidence in patients who are working to implement new dietary strategies (Nassim et al, 2020). Older adults require time and opportunity to explore alternative and favorable options that maintain culture and health, and nurses should assist them in identifying and exploring new options.…”
Section: Discussionmentioning
confidence: 99%
“…Further, individuals living with multiple chronic illnesses, including hypertension, may find it discouraging or difficult to select healthy foods that are best suited to their complex medical needs. Despite these challenges, studies have identified a strong interest in learning about the benefits of preparing and eating healthy foods as well as confidence in their ability to maintain healthy behaviors they had already mastered among older Black/African American women (Lucan et al, 2012; Nassim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%